(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2023)
At the present time in the conditions of integration and high competition in the world arena the role of human capital has increased significantly. In this regard, great emphasis is placed on universities, as the realized human capital, formed within the walls of the university, determines the main competitive advantages of the economy of the region and country, the possible trajectories of its further modernization and the level of innovative development. Managing the process of human capital formation and development is a number of specific measures to facilitate the process of transition to innovative economy and post-industrial society. The purpose of the article is to analyze the main trends in the management of human capital formation and development in the higher education system of Kazakhstan taking into account the transition of the economy to an innovative way of development. Answering the main research question about what changes in higher education at the global, global and local, state levels affect the formation and development of human capital at present, the authors, analyzing the current global trends of higher education development - mass privatization, internationalization, digitalization and ecosystem transformation of higher education, conclude that to ensure human capital development universities should become drivers of ecosystem development of higher education. For this purpose, educational institutions in the HE sphere should create a multipurpose and multidirectional environment for identification, selection, attraction, retention and enrichment of human resources, capable of innovative activity in order to transform them into human capital, ensuring victory in the competitive struggle. Universities become innovative platforms connecting all stakeholders of human capital development - business, state, education, human resources. In this regard, the development of partnership between HEIs and key stakeholders of the labor market: industrial partners, public authorities of all levels, organizations of non-profit sector and budget sphere, parent community and graduates of HE system is the best way to achieve the convergence of interests of all participants of social and labor relations for the benefit of socio-economic development of the country, its territories and individual subjects, large-scale accumulation and increase in human capital.